2018
DOI: 10.1111/ens.12313
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the morphological and ecological traits of Central European dung beetles

Abstract: Ecological, morphological and life‐history traits have been increasingly used in community ecology during the last decade. Dung beetles represent a model group of insects frequently used in studies of landscape ecology and grassland management. Their body sizes and nesting behavioral traits are regularly used to help understand ecological processes at the community level. However, information on their seasonal activity, wing morphometry and dung specialization is sparse in published reports, or is simply not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Open temperate habitats generally host more tunneller species than forest habitats, which is in contrast with most tropical regions where most species are adapted to forest conditions (Hanski & Cambefort, ). Tunnellers show a high variation in body mass and exhibit, on average, higher body mass than dwellers (Buse et al ., ). The abundance of large species explained variation in dung removal better than any other community measure along a disturbance gradient in Amazonian rainforest (Braga et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Open temperate habitats generally host more tunneller species than forest habitats, which is in contrast with most tropical regions where most species are adapted to forest conditions (Hanski & Cambefort, ). Tunnellers show a high variation in body mass and exhibit, on average, higher body mass than dwellers (Buse et al ., ). The abundance of large species explained variation in dung removal better than any other community measure along a disturbance gradient in Amazonian rainforest (Braga et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Table A1. List of species sampled with 12 dung-baited traps, their abundance and their respective traits: body mass, nesting strategy, length of activity period, and dung specialisation (Buse et al, 2018). LT, large tunneller; ST, small tunneller; SD, small dweller; LD, large dweller.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using various types of analyses to process data on around 80,000 individuals, we found that assemblages in wood pastures showed an intermediate or transient position between the assemblages of forests and pastures, which were distinct. In Central Europe, the majority of dung beetle species inhabit open or semiopen grasslands, and there are fewer woodland species [50] (Scarabaeinae: mostly grassland species, Geotrupidae: mostly forest species, Aphodiinae: both forest and grassland species [15]). Our study showed similar patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the Curculionidae feed exclusively on plants, including seeds, stems, flower heads and roots (Barratt, Cock & Oberprieler, 2018). The Aphodiidae is mainly detritivore, feeding on plant residue or dung produced by various animals (Finch et al, 2020;Buse et al, 2018). Generally speaking, the aforementioned three soil macro-faunal taxa could potentially survive on plants or plant residues.…”
Section: Specific Responses Of Different Taxa To the Variations In Enmentioning
confidence: 99%